The spatial concentration of domestic and foreign multinational corporate headquarters in Canada - Semple, R. (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1977)
This paper examines the spatial concentration of corporate power in Canada and measures the regional imbalances that are presently so noticeable. Furthermore, since corporate power in many instances is becoming ever more synonomous with foreign control the research notes not only the spatial concentration of this control but the sectors of the economy that are effectively under foreign domination.The paper intimates that those areas that house the headquarters of the giant multinational corporation are the net beneficiaries of the monetary strength, political leverage and technical expertise that these establishments have available to bring to bear in a wide variety of economic and political situations. It follows that if an area benefits from the presence of large corporations, and these same corporations are concentrated into particular regions then the possibility arises that certain "have-not" regions will have cause to feel left out of the mainstream of decision making that characterizes the economic and political well being of the entire nation. It appears that this joint problem of spatial concentration and sectoral domination by domestic as well as foreign corporations may be one of the many catalysts fostering both present-day Canadian nationalism and overt provincial sectionalism.